Psychological care needs for frontline nurses during the COVID-19 pandemic: A qualitative study - Ding, Chuanqi; Wang, Limin; Guo, Zhiting; Chen, Yun; Jin, Jingfen (Frontiers in Public Health, 2022)
Background In the course of the COVID-19 pandemic, nurses have played vital roles in clinical treatment. Their success in providing adequate care services depends on their psychological state, which determines their physical health, work status, therapeutic outcomes, and response to public health emergencies. However, a limited number of studies have evaluated psychological care needs from the perspective of nurses. This study aimed to describe the psychological care needs for frontline nurses in the course of the COVID-19 pandemic. Methods This was a qualitative descriptive study. Data were collected through semi-structured in-depth interviews with 15 frontline nurses who had been involved in the care of COVID-19 positive patients during the COVID-19 pandemic, and received psychological care. The conventional content analysis was used to identify themes from the interview transcripts. Results Four major themes about the psychological care needs of frontline nurses were identified: (1) psychological service providers (categories: professional service team, trustworthy person or group, ability to empathize with nurses); (2) problems with psychological care (categories: lack of universal screening and focused attention, online group counseling lacks targeting, psychological interventions lack individualization); (3) psychological care content (categories: mental health-related education, recognition of nurses' contributions, problem-solving therapy, psychological counseling and venting); (4) organization and management of psychological services (categories: focus on the psychological care needs of frontline nurses, build a standardized psychological service process system). Conclusion It is important to understand individual psychological care needs of frontline nurses and to provide them with tailor-made psychological care that meet their needs. This will improve their mental health, promote clinical care and quality responses to public health emergencies.